2020
DOI: 10.1002/mgg3.1200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways of diagnosis and prognosis in cervical cancer by bioinformatics analysis

Abstract: Background Cervical cancer as one of the most common malignant tumors lead to bad prognosis among women. Some researches already focus on the carcinogenesis and pathogenesis of cervical cancer, but it is still necessary to identify more key genes and pathways. Methods Differentially expressed genes were identified by GEO2R from the gene expression omnibus (GEO) website, then gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyzed by DAVID. Meanwhile, protein–protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…11 ). However, the high expression of CXCL8 [ 35 ], TNFAIP6 , CXCL5 and CDA in cervical cancer tissues was associated with a poor patient prognosis (Fig. 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 ). However, the high expression of CXCL8 [ 35 ], TNFAIP6 , CXCL5 and CDA in cervical cancer tissues was associated with a poor patient prognosis (Fig. 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis showed that NUSAP1 [ 36 ] , TOP2A, KIF2C [ 37 ] , NDC80 [ 23 ] , ASPM [ 21 , 38 ] , KIF20A [ 39 ] , CDK1 [ 19 , 38 ] , KIF11 [ 40 , 41 ] , BIRC5 [ 42 ] , MCM2 and CHEK1 [ 40 , 41 , 43 ] were high scoring hub genes and showed significantly upregulated expression in cervical cancer tissues compared with normal tissues ( P < 0.01). By analyzing the prognostic values of the hub genes from the 12 subnetworks, a total of 14 potential molecular targets ( MCM2 [ 23 , 35 , 44 46 ], TOP2A [ 19 , 35 , 40 ], BLM, RMI2 , EXO1 , RFC4 , PSCA , KNTC1 , CDC45 , GINS2 , CXCL8 , TNFAIP6 , CXCL5 , and CDA ) were obtained and annotated.…”
Section: Discussionmentioning
confidence: 99%
“…To improve our understanding of the molecular mechanisms underlying CC, bioinformatics analysis has been widely used to identify differentially expressed genes (DEGs), functional pathways and hub genes involved in the carcinogenesis and progression of CC. Although several genes have been identified in predicting the clinical outcome of CC, there have been inconsistencies between previous studies ( 10 , 11 ), which may be due to small sample sizes, heterogeneous histological subtypes, different detection platforms and various data processing methods. In the present study, three mRNA microarray datasets were downloaded from the Gene Expression Omnibus (GEO) database to acquire DEGs between CC and normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The DEGs were imported into Cytoscape software to realize the visualization of the PPI network (Yang et al, 2020). Mark the immune‐related DEGs, which were annotated in the STRING database in the PPI.…”
Section: Methodsmentioning
confidence: 99%